Acts of Creation: Thoughts on artistic research supervision - Frisk, Henrik; Johansson, Karin; Lindberg-Sand, Åsa (Höör Brutus Östlings Bokförlag Symposion, 2015)
Why do we need to think about artistic research supervision when doctoral supervision in general is such a well-established field? What particular skills are needed for a supervisor to get under the skin of an artistic research project? How can PhD candidates be guided so that the artistic projects develop fruitfully? What are the ethical implications of supervising an artistic research project? What is the meaning of method and theory in this kind of research? And how will the supervisors contribute to the development of the field of artistic research?The texts in this anthology comprise the results of discussions between a group of supervisors at Konstnärliga forskarskolan, the Swedish artistic research school over the past few years. They reflect the need for rethinking traditional principles, procedures and structures in the complex field of artistic research supervision. From a variety of perspectives, the authors share experiences and future visions that may contribute to a continued discussion on the further development of artistic research.
Keywords: Artistic research; Education